Собрание сочинений: в 3 томах : перевод с эстонского (Пауль Куусберг) - Куусберг Пауль Аугустович (1986)
Экземпляры: КХ (20211025) / Инвентарный номер: 884758 / Сис.шифр: С(Эст) / Авт.знак: К 95 / ГРНТИ: 17 / ББК: 84(4Эст)-4